Arthrogryposis Congenita and Hepatorenal Abnormalities - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Arthrogryposis multiplex congenita with renal and hepatic abnormalities, demonstrated at autopsy in a two month old child of consanguineous parents, is reported from the Pediatric Hospital, Coimbra, Portugal.